Interpretation and allegory : antiquity to the modern period - Whitman, Jon, 1949- (Brill's studies in intellectual history, 2000)
An investigation of the theory and practice of interpretation. Concentrating on interpretive allegory, the volume opens and organizes new approaches to over 2000 years of critical change. Its topics extend from pagan, Jewish, Christian, and Islamic perspectives to postmodern inquiries.